PENGEMBANGAN LEMBAR KERJA SISWA DENGAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA - Lase, Shinta Putri Angraeni; Sadiana Lase; Netti Kariani Mendrofa; Ratna Natalia Mendrofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on initial observations at the UPTD SMP Negeri 1 Gunungsitoli Selatan and the results obtained that students’ mathematical reasoning abilities were in the low category and the teaching materials used were still limited. Students had difficulty understanding the textbooks that were too advanced and relied solely on teachers in the learning process. The solution to this problem was to use teaching materials in the form of simple student worksheet, so they were easy for students to understand. The purpose of this research was to develop student worksheet with a realistic mathematics learning approach that was valid, practical, and effective in improving students’ mathematical reasoning abilities. This research is a development research. The development model used is the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The instruments in this study were learning outcome tests, validation questionnaires, and response questionnaires, and response questionnaires. The types of data used in this study are qualitative and quantitative data. Qualitative data consist of comments and suggestions provided by the validator regarding the developed student worksheet. Meanwhile, quantitative data consist of questionnaire results from the validator, student and teacher response questionnaires, and learning outcome tests. Based on the research results, the developed student worksheet have been tested and declared valid in terms of material validity (content), language validity, and design validity. Furthermore, the student worksheet are also very practical to use by students with a practicality percentage of 91% and a practicality percentage result from the teacher of 97.5%. The student worksheets are also effective in improving students’ mathematical reasoning abilities with an average score of 77.20 in the high category and a classical completeness percentage of 86.20 in the very effective category. So it can be concluded that the student worksheets with a realistic mathematical learning approach developed have met the expectations or objectives.